1998
DOI: 10.1002/(sici)1097-0215(19980812)77:4<528::aid-ijc9>3.3.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and magnesium in drinking water and risk of death from rectal cancer

Abstract: The possible association between the risk of rectal cancer and the levels of calcium and magnesium in drinking water from municipal supplies was investigated in a matched casecontrol study in Taiwan. All eligible rectal-cancer deaths (986 cases) of Taiwan residents from 1990 through 1994 were compared with a sample of deaths from other causes (986 controls), and the levels of calcium and magnesium in the drinking water of these residents were determined. Data on calcium and magnesium levels in drinking water t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Our finding of a null association between total magnesium intake and colorectal cancer incidence is in agreement with an Asian case-control study, which observed no association between magnesium intake in drinking water and death from cancers of the colon (10) and rectum (11). However, both the Swedish cohort study and the Iowa Women's Health Study reported an inverse association between total magnesium intake and colon cancer risk (12,13), with the Swedish cohort study also reporting an inverse association with rectal cancer risk (12).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our finding of a null association between total magnesium intake and colorectal cancer incidence is in agreement with an Asian case-control study, which observed no association between magnesium intake in drinking water and death from cancers of the colon (10) and rectum (11). However, both the Swedish cohort study and the Iowa Women's Health Study reported an inverse association between total magnesium intake and colon cancer risk (12,13), with the Swedish cohort study also reporting an inverse association with rectal cancer risk (12).…”
Section: Discussionsupporting
confidence: 89%
“…A case-control study found that magnesium level in drinking water was not associated with death from cancers of the colon (10) and rectum (11). On the basis of a dietary questionnaire, however, two recent prospective studies observed an inverse association between total magnesium intake and incident colorectal cancer (12,13), although one study reported that the inverse association was only limited to colon cancer (13).…”
Section: Introductionmentioning
confidence: 99%
“…High levels of magnesium in drinking water protect against oesophageal and liver cancer, and it is inversely correlated with death from breast, prostate, and ovarian cancers, whereas no correlation existed for other tumours [14]. Dietary magnesium intake has been reported to have a statistically significant nonlinear inverse association with the risk of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the evident link between magnesium and cell proliferation, the role of magnesium in cancer cells is scarcely documented and often contradictory [13][14][15]; in particular, the role of magnesium in primary bone tumours has not yet been examined. It is worth noting that in physiological conditions, magnesium plays an important role in bone metabolism [16][17][18] and can influence osteoblast and osteoclast differentiation, affecting bone growth and remodelling [19,20].…”
Section: Introductionmentioning
confidence: 99%